2016
DOI: 10.2139/ssrn.2767342
|View full text |Cite
|
Sign up to set email alerts
|

Housing Markets and Housing Policies in India

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…It is reported that there is a housing demand of almost 19 million housing units in India's urban areas, according to 2011 census. Within existing city centers, a breakdown shows that 80% of the demand comes from the need for replacement houses among people living in overcrowded or congested conditions (conditions deemed as unfit for living), and only 5% of it comes from homeless people (Kundu, 2012;Tiwari & Rao, 2016). This demand when analyzed at a state level reveals that the states of Utter Pradesh and Maharashtra (home states of Delhi and Mumbai) are most in need of urban housing.…”
Section: An Historical Analysis Of the Housing Demand In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that there is a housing demand of almost 19 million housing units in India's urban areas, according to 2011 census. Within existing city centers, a breakdown shows that 80% of the demand comes from the need for replacement houses among people living in overcrowded or congested conditions (conditions deemed as unfit for living), and only 5% of it comes from homeless people (Kundu, 2012;Tiwari & Rao, 2016). This demand when analyzed at a state level reveals that the states of Utter Pradesh and Maharashtra (home states of Delhi and Mumbai) are most in need of urban housing.…”
Section: An Historical Analysis Of the Housing Demand In Indiamentioning
confidence: 99%
“…This process involved forceful evictions that often resulted in resettling the evicted in remote areas outside cities or on the periphery. This relocation made life more difficult for the already economically disadvantaged population as they were disconnected from their work places and public infrastructure, therefore, they often returned to squatting within the city limits (Tiwari & Rao, 2016).…”
Section: India's Approach In Phase One Of Housing Policy and Limitatimentioning
confidence: 99%
“…The high demand of building materials and resources due to mass housing construction activities led to their increased costs which eventually shrank the construction industry, slowing down the construction process. This scenario put added pressure on the existing housing stock raising the prices and making it unaffordable to the poor (Tiwari and Rao 2016). The government tried to control prices by introducing regulations like the legislative control act on rent (the Rental Control Act).…”
Section: India's Approach In Phase 1 Of Housing Policymentioning
confidence: 99%
“…This act backfired in the sense that the private sector seeing no monetary incentive or growth in the rental opportunities refused to invest in them, which led to limited rental options for the poor. This shortfall in housing was compensated by people settling informally in and around cities, creating crowded and unplanned settlements, which in the absence of any public infrastructure and support, often turned into slum-like conditions (Tiwari and Rao 2016).The strategy of clearing the appalling living conditions through forceful evictions often resulted in resettling the evicted in remote areas outside cities or on the periphery, where they upon finding life more difficult, being disconnected from their work places and public infrastructure, frequently returned to squatting within the city limits.…”
Section: India's Approach In Phase 1 Of Housing Policymentioning
confidence: 99%
“…As per the Report of the Technical Group on Housing Shortage for the Twelfth Plan Period the estimated housing shortage in urban areas is 18.78 million housing units. However, the existing housing shortfall gets increased by 3 million at 21.87 million units with the inclusion of nondurable houses [6]. In the post-independence era, the government has made various efforts for housing development by establishing different institutes such as HUDCO, National Buildings Organisation (NBO), Central Public Works Department etc.…”
Section: Introductionmentioning
confidence: 99%